Selective Self-Presentation on Video-Mediated Communication: A Study of Hyperpersonal Communication - Palupi Palupi (MediaTor (Jurnal Komunikasi), 2019)
The development of Internet and communication technology has been increasing from time to time. Humans around the globe are connected to digital communication device. Technology has been growing and changing the way people communicate; from text-based computer-mediated communication to video-mediated communication. The study is conducted to determine whether the online users in VMC perform selective self-presentation under conditions when nonverbal cues are present and the interlocutor is not anonymous. This study is a qualitative research with semi-structured interview as its method. Findings in this study showed that participants perform selective self-presentation in VMC. By wearing veil for females or combing hair for males, tiding up the room and table, choosing certain place, also hiding something from the web camera scope are the ways they present themselves to obtain good impression and avoid bad impression from interlocutorsThe findings also discovered that participants perform selective self-presentation to ordinary friends, colleagues, or acquaintances with the same way and the same reason why they perform it when nonverbal cues are present. However, participants do not perform selective self-presentation to family and close friends.